2002
DOI: 10.1161/01.atv.0000042456.84190.f0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Association of Tissue Factor Pathway Inhibitor With Human Placenta

Abstract: Objective-Tissue factor pathway inhibitor (TFPI) is an endothelial-associated inhibitor of blood coagulation. Because the mechanism for attachment of TFPI to endothelium is not clear, we investigated its association with human placenta. Methods and Results-Western blots demonstrate that treatment with phosphatidylinositol-specific phospholipase C (PIPLC) removes more placental TFPI than either PBS or heparin, a finding confirmed by immunohistochemistry. The amounts of heparin-releasable and PIPLC-releasable TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 29 publications
2
54
2
Order By: Relevance
“…22 It has been reported that TFPI␤ is not produced by human endothelial EAhy926 cells. 23 The cell surface association of TFPI␣ was thought to involve its interaction with a separate, as yet unidentified, GPI-anchored coreceptor(s) [15][16][17][20][21][22][23] that may control its cellular trafficking and surface expression. 21 As we initiated studies intended to identify the putative GPI-anchored coreceptor(s) for TFPI␣¸our results led to the realization that TFPI␤, rather than TFPI␣, is the dominant PIPLC-releasable isoform on endothelial cells and placental microsomes.…”
mentioning
confidence: 99%
“…22 It has been reported that TFPI␤ is not produced by human endothelial EAhy926 cells. 23 The cell surface association of TFPI␣ was thought to involve its interaction with a separate, as yet unidentified, GPI-anchored coreceptor(s) [15][16][17][20][21][22][23] that may control its cellular trafficking and surface expression. 21 As we initiated studies intended to identify the putative GPI-anchored coreceptor(s) for TFPI␣¸our results led to the realization that TFPI␤, rather than TFPI␣, is the dominant PIPLC-releasable isoform on endothelial cells and placental microsomes.…”
mentioning
confidence: 99%
“…TFPIalpha associates with the endothelium surface in two ways. About 90% is indirectly bound through an, as yet, unident4ified GPI-anchored protein 16,17 . The association of TFPIalpha with endothelium through a GPI-anchored protein localizes TFPI to caveolae, where it may interact with caveolin-1 which increases its surface expression and anticoagulant activity 18 .…”
Section: Alternatively Spliced Forms Of Tfpimentioning
confidence: 99%
“…The association of TFPIalpha with endothelium through a GPI-anchored protein localizes TFPI to caveolae, where it may interact with caveolin-1 which increases its surface expression and anticoagulant activity 18 . The remaining 10% of TFPIalpha is nonspecifically bound to cell surface glycosaminoglycans 17 . In humans, the glycosaminoglycan bound TFPI alpha is released into plasma following heparin infusion causing the plasma TFPI concentration to increase 2-to 4-fold 19,20 .…”
Section: Alternatively Spliced Forms Of Tfpimentioning
confidence: 99%
See 1 more Smart Citation
“…Its biosynthesis is associated primarily with the microvascular endothelium (10,11). The TFPI molecule contains three consecutive Kunitztype protease inhibitor domains, and the second domain (K2) connects and inhibits the Xa factor, and the first (K1) -with the tenase complex (TF/FVIIa) (12,13).…”
Section: Introductionmentioning
confidence: 99%